The Role and Challenges of A Mediator To Resolve The International Conflict in The Digital Era (Case Study: The Role of OANA) - Brilliant Windy Khairunnisa (Syntax Corporation Indonesia, 2021)
The digital era has been born from the influence of globalization. In this digital era, international relations are beginning to be affected by the existence of various new ways to do diplomacy. Where diplomacy carried out by each country feels easier than in previous eras, communication can also be carried out without having to take a long time, especially when delivering meeting appointments or being willing to attend a meeting. Along with the development of this digital era, the role of third parties in resolving a conflict will also become easier, especially from mediators who are often the liaison between the two countries in conflict. This research was conducted to reveal perspectives related to the role and challenges for mediators in carrying out international conflict resolution in the digital era that continues to progress. The method used is a qualitative research method by presenting secondary data. The results show that the role of the mediator in resolving conflicts will be significantly more challenging because of digital factors that can take conflict actions online or provide fake news and can be widely spread throughout the country in an instant with ease.